(untitled) (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Urinary tract infections (UTIs) are very common among Indian population which can be acute or chronic. However, untreated UTIs can lead to chronic condition which ultimately causes hospitalization. Objective: The present study aimed to study the comparison of three different methods of detection of biofilm production by uropathogens in tropical catheterized patients. Materials and Methods: The study included 500 tropical catheterized patients admitted in Civil Hospital, Ambala City. All the patients were interviewed as per a pre-defined protocol, and all the required medical informations were recorded in a pre-determined format for easy extraction as well as interpretations. Samples were collected for the tests to identify the microorganisms in the isolates and also to detect the biofilm product. Identification of microorganisms was performed by routine methods. Three different methods, namely tissue culture plate method (TCPM), tube adherence method (TAM), and modified Congo red agar (MCRA) method, were used to detection the biofilm production and compared. Results and Discussion: The results suggested that Escherichia coli is the most predominant uropathogen responsible for UTIs in the catheterized patients in the present studied patient population. Of these isolates, resistant E. coli cases were found to be most abundant and strong biofilm producer. Conclusion: TCPM was found to be significant method for the detection of biofilm production in this patient population, especially when the causative organism is resistant E. coli followed by TAM and MCRA method.